82 YEARS SINCE THE BATTLE OF STALINGRAD - Gheorghe BOARU (Annals: Series on Military Sciences)
The "Battle of Stalingrad" was the bloodiest battle of World War II. It was the "battle of battles" on the Eastern Front, considered by some historians to be the "Verdun of the Volga". It was probably the engagement whose outcome shaped the history of the European continent for decades to come. The "Battle of Stalingrad" is a phrase known in historiography as the great military confrontation on the Don and Volga, which took place in the second half of 1942 (from July 17) and the beginning of 1943 (February 2), and which involved the Romanian 3rd Army south of the Don River and implicitly in the Don Bend, the Romanian 4th Army in the Kalmuc Steppe (south of Stalingrad) and several large Romanian units in Stalingrad itself. In this "battle" Romania had a significant participation in terms of military and material forces but also through the very heavy losses suffered.